THE INFLUENCE OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE ON INTENTION IN USING SHOPEEPAY MEDIATED BY TRUST - Pamungkas, Linda; Welsa, Henny; Hutami, Lusia Tria Hatmanti (Jurnal Perilaku dan Strategi Bisnis, 2023)
In this era of industry 4.0, the big impetus for the movement towards digital seems to appear in many aspects of life. This can be seen from the growth in online transactions, which has also driven the digitalization of the payment system. This research aims to determine the influence of perceived usefulness, perceived ease of use on usage intention of ShopeePay mediated by trust. This type of research is quantitative and processing using SPSS. The sample of this study refers to the population above which in its determination requires the following criteria: UST students, ShopeePay users; ShopeePay users as above use this e-wallet to pay for purchases at Shopee; and in the last few months have used ShopeePay to shop at Shopee at least 1 transaction. The analysis uses regression analysis, before the hypothesis test (t test) is carried out, the researcher performs a validation test, a reliability test, and a classical assumption test. The processing results prove that the five hypotheses have a significant effect. Based on the results of the Sobel test, trust is proven to mediate perceived usefulness on usage intentions and perceived ease of use on usage intentions. Electronic payment systems such as digital cash, debit or credit cards, and electronic wallets (e-wallets) have benefited consumers in conducting non-cash transactions. Advice for further research is expected to expand the results of this study by involving other variables in the form of moderating or other intervening variables.